Rancang Bangun Aplikasi Seleksi Penerimaan Mahasiswa Baru Pada STIKES Yayasan RS. Dr. Soetomo Surabaya - Permana, Marco Teguh; tiowati, Sulis; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract: One indicator of the success of the process of selection of new admissions is information about the results of a complete and accurate selection . During the selection process of new students are still using manual processes and not computerized . In addition , there are still obstacles with the students entrusted and the presence of various factors such as fatigue due to the amount of work piling up , so that errors can arise in the process of selection of new admissions. Application selection of new admissions is a development that is used to handle all obstacles and problems in the selection process for new students is on STIKES Hospital Foundation . Dr. Soetomo . Type selection is handled by the application 's selection of new admissions there are two types of values and questions . Application selection of new admissions system is created dynamically , so that in the future if there are additional categories of test users can add it easily. Once tested and implemented to users in STIKES Hospital Foundation . Dr Soetomo , selection of new admissions applications this may help the assessment team work . This is evident from the application to facilitate preparation of reports required by the leadership to assist in decision making. Keywords: Applications , Selection , Admissions.